Pengamatan Kualitas Pada Perairan Sungai Boyo Kota Gunungsitoli - Mendrofa, Cevin Wirnata (CV. SINAR HOWUHOWU, 2025)
This study aims to observe the physical parameters of the Boyo River waters in order to assess the water quality and condition of the river's aquatic ecosystem. Observations were carried out at several observation points along the Boyo River by measuring physical parameters including temperature, pH, turbidity, salinity, and water flow velocity. The results showed that the water temperature in the Boyo River tends to fluctuate depending on the season, with higher temperatures in the dry season. The pH value of the water is mostly within the normal range, although there are indications of a decrease in pH at several points that can be influenced by domestic waste and agricultural activities. Water turbidity is relatively high, especially in areas close to settlements and agricultural land, indicating sedimentation and pollution. Water salinity shows low values at most points, except in the downstream of the river which is affected by seawater intrusion. The speed of water flow varies, with higher speeds in the upstream and slower downstream. Based on the results of observations, the water quality of the Boyo River shows challenges related to pollution and seasonal changes, which affect the balance of the ecosystem. Therefore, continuous monitoring and better management of water quality are needed to support the sustainability of the ecosystem and the utilization of river aquatic resources.